Krakowski dwór opata cystersów z Mogiły z XIII wieku na tle źródeł historycznych i archeologicznych dotyczących innych krakowskich siedzib opatów mogilskich .......... 167 - Niemiec, Dariusz (Dzieje i kultura Cystersów w Polsce, 2025)
THE 13TH CENTURY KRAKÓW MANOR HOUSE OF THE CISTERCIAN ABBOT OF MOGIŁA AGAINST THE BACKGROUND OF HISTORICAL AND ARCHAEOLOGICAL SOURCES CONCERNING OTHER KRAKÓW ABBOTS OF MOGIŁA It is known from written sources that even before 1299 a brick manor house must have been built in Kraków for the urban residence of the Cistercian abbot of Mogiła. This building is referred to as domum lapideam fratrum de Mugila in 1313. From the content of the settlement concluded by the Cistercians with the city council in 1428 and from Jan Długosz’s description in the Liber beneficiorum, we can also infer the direct vicinity of the Kraków Cistercian manor house with the Duchy hospital, which makes it possible to identify it with the exquisitely preserved three-story tenement used since the 19th century by the rectory of the Holy Cross parish. The paper brings together the entirety of medieval and early modern written and iconographic accounts of the said building, and discusses the stylistic links between the original historic substance of the building and 13th-century Cistercian architecture.